EyeRIS eye resemblance by indication of similarity - Celeste, Nherrisa Mae U.; Yang, Genny R. (2008)
In this study, the challenge of image processing is implemented using a simple Region Growing Algorithm. A curve detection algorithm is also implemented using the Lagrange's Formula for interpolating polynomials and the Least Mean Square Concept of Approximation. Lastly, a simple circle detection algorithm is also used. The Region Growing Algorithm works by first looking for a seed pixel and basing on that pixel, it compares the color of the pixels around it, determining if the pixel compared belongs to the same region as the seed pixel by testing a threshold. The mathematical formulas are implemented to find for comparison between curves found in the eye. Circle detection is done by looking for the diameter based on colors. The research study is effective because it uses a simpler algorithm in determining the similarity percentage between two eye images.